Invasive micropapillary carcinoma of the breast: Case report - (:unkn) unknown (My University, 2004)
Invasive micropapillary carcinoma (IMPC) is a recently reported entity that is a histological variant of breast cancer with a poor prognosis. The tumor is best characterized by a nested pattern of eosinophilic tumor cells aranged in a solid, morular , tubular pattern. The tumor cells have intermediate to high grade nuclei and individual groups have a clear space separating them from the surrounding stroma. We report one case of pure IMPC of the breast.
Keywords: Breast; Carcinoma; Micropapillary carcinoma; Pathology